ANALISIS PENGARUH KOMPONEN TEKNOLOGI DAN NILAI TAMBAH TERHADAP PERKEMBANGAN SENTRA INDUSTRI KERUPUK UDANG SIDOARJO (STUDI KASUS DI INDUSTRI KERUPUK UDANG DESA KEDUNGREJO, KABUPATEN SIDOARJO) - Mentari Ingranti; Imam Santoso; Wike Agustin Prima Dania (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2012)
Small and Medium Enterprises is one of the essential sectors for an economy in a state. The existence of centre can ease the occurrence of new businesses with the availability of productive resources in industry sector. Industry centre it self aims to cluster several businesses which have similar natures. Technology components (technoware, humanware, inforware, orgaware) are a way to assess to what extent an industry centre can develop. The aims of the research are the influence of technology components to the development industry centre and to get some additional values from production process. The respondents in this study are 33 industries in Kedungrejo industry centre. Partial Least Squares (PLS) is used as the data analysis method. PLS method can be used in every scale of data and the sample does not have to be in large amount. The result gained by analyzing with PLS is that among, technoware is the technology compenent which has highest influence to the development of industry centre. The score of this compenent is 0,520 ant the margin of product additional value is IDR 82,500.Keywords : Industrial districts, Technology components, PLS.